MANAJEMEN STRATEGI PEMASARAN PENDIDIKAN BERBASIS BUDAYA RELIGIUS STUDI KASUS DI SMA NEGERI 1 PAITON - Rohimah, Siti Baitir (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2023)
In summary, the purpose of this study is to ascertain how Paiton 1 state high school manages the marketing of its religious culture-based education services. This study used a qualitative approach.field technique. Utilizing snowball and purposive selection procedures, the samples were selected. Interviews, observations, and documentation procedures were used to gather the data. In this research. Using an inductive methodology and descriptive-qualitative data analysis, the researcher study the information. The findings of this study showed that: (1) Paiton 1 state high school carries out marketing management based on religious culture to meet the needs of education customers who will create a generation of Muslims with strong and noble characters, who master the principles, have a scientific foundation, who contribute to the welfare of the world, and who are devoted to Allah SWT. (2) Through the inclusion of monotheism, the Shari'ah, and morality in the curriculum, vision, mission, school purpose, school programs, and the learning process, schools establish religious culture. (3) Paiton 1 state high school is supported in marketing education services by the following factors: a. The independent curriculum application; b. qualified human resources; c. comprehensive educational facilities; d.Promotional initiatives that employ a variety of tactics; accessible school sites; and f. a list of accomplishments in the public and religious spheres.